Analisis Faktor – Faktor Yang Mempengaruhi Keputusan Mahasiswa Memilih Melanjutkan Pendidikan Strata-1 Ekonomi Islam Universitas Diponegoro - Firdaus Helmi Adam; Agus Hariyanto (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the effect of tuition fees, promotions, facilities, infrastructure, and also reputation on student decision-making in choosing the Islamic Economics study program, at the Faculty of Economics and Business (FEB) Diponegoro University, Semarang. This study uses a quantitative approach. The variables used in this study are tuition fees, promotions, facilities, and infrastructure, reputation, decision-making. The method used in this study was by taking questionnaire data which was distributed to active students of the Islamic Economics study program at Diponegoro University. The population used in this study is the number of active students in 2019, 2020, 2021, and 2022 which total 615 students. The samples taken were 97 students using the proportional random sampling technique. This study used multiple linear regression which was processed using the Statistical Package for Social Science (SPSS) version 26. The results showed that the infrastructure and reputation variables influenced student decision-making in choosing a study program, but the tuition and promotion variables did not affect student decisions in choosing the Islamic Economics study program, Faculty of Economics and Business (FEB) Diponegoro University Semarang.